TINJAUAN YURIDIS HAK MILIK ATAS APARTEMEN/RUMAH SUSUN KEPADA WARGA ASING DI INDONESIA - Damanik, Yohana Dwi Putri; Manurung, Ribka Rosalia; Sihombing, Maria Vatresya; Aisyah, Irnadia; Yamani, M. (LPPM Universitas Bina Bangsa, 2025)
Foreign Citizens (WNA) or what are also called foreigners, namely people who are not Indonesian citizens, can also have rights to ownership of apartments or flats located in Indonesia. With the enactment of the Job Creation Law, there have been several changes to regulations relating to land and housing, one of which is the regulation of ownership of apartment units by foreign citizens residing in Indonesia. This research aims to determine the juridical review of ownership rights to apartments/flats for foreign citizens in Indonesia. The method used in this research is normative. The data collection technique used is document study. The research results show that Government Regulation no. 18 of 2021 in Article 67 paragraph (1) letter c which states that